A centrosome interactome provides insight into organelle assembly and reveals a non-duplication role for Plk4. - Galletta, B.J.; Fagerstrom, C.J.; Schoborg, T.A.; McLamarrah, T.A.; Ryniawec, J.M.; Buster, D.W.; Slep, K.C.; Rogers, G.C.; Rusan, N.M. (Nature communications, 2016)
The centrosome is the major microtubule-organizing centre of many cells, best known for its role in mitotic spindle organization. How the proteins of the centrosome are accurately assembled to carry out its many functions remains poorly understood. The non-membrane-bound nature of the centrosome dictates that protein-protein interactions drive its assembly and functions. To investigate this massive macromolecular organelle, we generated a 'domain-level' centrosome interactome using direct protein-protein interaction data from a focused yeast two-hybrid screen. We then used biochemistry, cell biology and the model organism Drosophila to provide insight into the protein organization and kinase regulatory machinery required for centrosome assembly. Finally, we identified a novel role for Plk4, the master regulator of centriole duplication. We show that Plk4 phosphorylates Cep135 to properly position the essential centriole component Asterless. This interaction landscape affords a critical framework for research of normal and aberrant centrosomes.